Association between antithrombotic treatment and outcomes at 1-year follow-up in patients with atrial fibrillation: the EORP-AF General Long-Term Registry - Boriani, Giuseppe; Proietti, Marco; Laroche, Cécile; Fauchier, Laurent; Marin, Francisco; Nabauer, Michael; Potpara, Tatjana; Dan, Gheorghe-Andrei; Kalarus, Zbigniew; Tavazzi, Luigi; Maggioni, Aldo P; Lip, Gregory Y H and collaborators; et al. (Oxford University Press (OUP), 2019)
In recent years, stroke prevention in patients with atrial fibrillation (AF) has radically changed, with increasing use of non-vitamin K antagonist oral anticoagulants (NOACs). Contemporary European data on AF thromboprophylaxis are needed.
Keywords: stroke prevention; atrial fibrillation; NOACs